1993
DOI: 10.1111/j.1600-0749.1993.tb00591.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Chemicals and Melanin

Abstract: Various drugs and other chemicals, such as organic amines, metals, polycyclic aromatic hydrocarbons, etc., are bound to melanin and retained in pigmented tissues for long periods. The physiological significance of the binding is not evident, but it has been suggested that the melanin protects the pigmented cells and adjacent tissues by adsorbing potentially harmful substances, which then are slowly released in nontoxic concentrations. Long-term exposure, on the other hand, may build up high levels of noxious c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
183
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(190 citation statements)
references
References 62 publications
5
183
2
Order By: Relevance
“…The linewidths changed after the UVA irradiation of DOPA-melanin-moxifl oxacin complexes [19]. Linewidths of melanin polymers changed after drug binding to melanin [16][17][18][19][20][21] and metal ions [11][12][13][14][15].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The linewidths changed after the UVA irradiation of DOPA-melanin-moxifl oxacin complexes [19]. Linewidths of melanin polymers changed after drug binding to melanin [16][17][18][19][20][21] and metal ions [11][12][13][14][15].…”
Section: Resultsmentioning
confidence: 99%
“…Electron paramagnetic resonance (EPR) investigations confi rmed the existence of free radicals in melanins [1][2][3][4][5][6][7][8][9][10], and melanin complexes with metal ions [1,7,[11][12][13][14][15] and drugs [7,12,[16][17][18][19][20][21]. Dia-and paramagnetic metal ions [11][12][13][14][15] and pharmacological substances [16][17][18][19][20][21] change the intensity of EPR lines of melanin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, hair may reflect tissue metal concentrations. Additionally, melanin pigments can bind cations by ionic interaction at physiological pHs because melanin are polyanionic polymers containing negatively charged carboxyl groups and semiquinones (Larsson, 1993). Moreover, uncharged metals, such as elemental Hg, may also bind to the hydrophobic core of the melanin polymer in the hair structure (Kronstrand et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…5), can be explained by the ability of flumequine to complex with divalent ions (like Ca 2+ and Mg 2+ ). The affinity of flumequine for skin can be explained by melanin's capacity to bind drugs (Potts 1963, Ullberg et al 1970, Lindquist & Ullberg 1972, Larsson 1993, Fukuda & Sasaki 1994, Howells et al 1994, Salazarbookaman et al 1994. Several studies have reported residues of flumequine and other fluoroquinolones in bone and skin for a long time after the level is below detection in plasma/muscle (Steffenak et al 1991, van der Heijden et al 1993, Elema et al 1994, Martinsen et al 1994.…”
Section: Skin Eye Bilementioning
confidence: 99%